2019
DOI: 10.3390/rs11101170
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatiotemporal Variation in Land Subsidence on the Beijing Plain, China

Abstract: Since the 1970s, land subsidence has been rapidly developing on the Beijing Plain, and the systematic study of the evolutionary mechanism of this subsidence is of great significance in the sustainable development of the regional economy. On the basis of Interferometric Synthetic Aperture Radar (InSAR) results, this study employed the Mann–Kendall method for the first time to determine the mutation information of land subsidence on the Beijing Plain from 2004 to 2015. By combining the hydrogeological conditions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Over the past few decades, interferometric synthetic aperture radar (InSAR) has been developed as an effective geodetic surveying technique and used for investigating geophysical phenomena, including seismic deformation [18,19], volcano dynamics [20,21], earthquakes [22,23], landslides [24,25], and other geologic processes. The InSAR technique can also monitor the ground deformation caused by human activities (e.g., mining [26,27], delta sinking [28], and land subsidence [29][30][31][32]). Ground fissure is commonly a secondary environmental geological problem caused by land subsidence [33] and the InSAR technique can provide a new tool for investigating ground fissure activity [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, interferometric synthetic aperture radar (InSAR) has been developed as an effective geodetic surveying technique and used for investigating geophysical phenomena, including seismic deformation [18,19], volcano dynamics [20,21], earthquakes [22,23], landslides [24,25], and other geologic processes. The InSAR technique can also monitor the ground deformation caused by human activities (e.g., mining [26,27], delta sinking [28], and land subsidence [29][30][31][32]). Ground fissure is commonly a secondary environmental geological problem caused by land subsidence [33] and the InSAR technique can provide a new tool for investigating ground fissure activity [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…1). The locations and the hydrogeological conditions of the study region are described in detail in a previous study (Guo et al, 2019). The ground subsidence in Beijing began in 1935, and the main subsidence regions were located in Xidan and Dongdan.…”
Section: Study Areamentioning
confidence: 99%
“…Compared with traditional technology, InSAR has the advantages of a wide monitoring range and high monitoring accuracy and has been widely used in ground subsidence monitoring research by experts and scholars (Castellazzi et al, 2016;Albano et al, 2016;Amighpey et al, 2016;Dehghani et al, 2013;Ge et al, 2014;Da Lio and Tosi, 2018?). In 2002and 2004 proposed the small baseline set interferometry-interferometric synthetic aperture radar (SBAS-InSAR) technique, which is more suitable for long time, slow deformation surface monitoring (Berardino et al, 2002;Lanari et al, 2004). Subsequently, experts and schol- ars have used this technology to select multisource SAR data, such as ENVISAT ASAR and COSMO-SkyMed, and have used these data to monitor the surface deformation of the Gulf of Naples (Solari et al, 2018), Los Angeles (Chilingar and Endres, 2005), Central Mexico and other areas (Castellazzi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The discrete deformation rates variation values are obtained by Eq. (3), and the discrete values are fitted by the fitting model (Júnior et al, 2006). Commonly used fitting models include exponential, spherical, gaussian, and the linear model.…”
Section: Geographical Semi-variogram Analysismentioning
confidence: 99%
“…Researches have shown that groundwater level, the geology background including the thickness of the compressible layer and aquifer structure have a strong relationship with the land subsidence. Guo et al (2019) worked on the temporal mutation of land subsidence through the Mann-Kendall method, which is a nonparametric statistical method to evaluate the trend changes of time series. She found that about 50 % of the grids mutated in 2015, the main reason is the implement of the "South-to-North Water Transfer Middle Line" project, which diverted 703 million cubic meters of water to Beijing from 2014 to 2015.…”
Section: Introductionmentioning
confidence: 99%